A MODIFICATION LIMIT EQUILIBRUM SOLUTION FOR MINE BACKFILL ANALYSIS IN SEMI CUBE STOPE - Kahfi, Ashabul; Oktaviani, Revia; Devy, Shalaho Dina (PERHAPI, 2024)
Mine backfill is a material that is used to fill the empty stope in an underground mine for ground control stability and to reduce ore dilution. Generally, the backfill consists of mining waste materials and ore tailings, which are added to a binder such as cement. Problems that often appear in the mining cycle using stope and backfill are the stability of the backfill on the primary stope when exposing the secondary stope. Previous researchers suggested analyzing the stability of the backfill on the narrow stope. In some cases, a semi-cube stope is often found. Obviously, the potential failure dimension, which acts as the driving force of the backfill in the semi-cube stope, is smaller than the narrow stope. This study was meant to develop a method for analyzing the stability of the backfill on the semi-cube stope by calculating the driving force according to the failure potential dimensions that could potentially occur and simulating it with numerical modeling using FEM.